COMMUTATIVE AND SPECTRAL PROPERTIES OF kth-ORDER (SLANT TOEPLITZ + SLANT HANKEL) OPERATORS ON THE POLYDISK - Singh, M. P.; Laishram, Pradipkumar; Singh, Oinam Nilbir (Journal of the Indonesian Mathematical Society, 2024)
In this paper for k ≥2, we introduce the idea of kth-order (Slant Toeplitz + Slant Hankel ) operators on the polydisk and discuss the commutativity, partial isometry and co-isometry properties. Further, we extend our study to the spectral properties.